2019
DOI: 10.1002/ar.24181
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Cell–Cell Communication in the Cornea

Abstract: One question that has intrigued cell biologists for many years is, "How do cells interact to influence one another's activity?" The discovery of extracellular vesicles (EVs) and the fact that they carry cargo, which directs cells to undergo changes in morphology and gene expression, has revolutionized this field of research. Little is known regarding the role of EVs in the cornea; however, we have demonstrated that EVs isolated from corneal epithelial cells direct corneal keratocytes to initiate fibrosis. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…We found that our corneal co-culture constructs re-capitulated epithelial-stromal interactions during wound healing with clear evidence of extracellular vesicle secretion and deposition of provisional matrix proteins between epithelial and stromal layers. Similar to our findings using endothelial-stromal co-cultures [46], diffusion and uptake of extracellular vesicles within the stroma appeared to occur, suggesting that vesicle migration is not inhibited or limited by the stromal ECM, which is composed predominately of collagen types I and V. The use of this co-culture system as a model of human wound repair has many advantages: (1) it uses human cells and can be easily manipulated to knock-in or -down genes in either the hCEC or hCF; (2) by treating the cultures with EDTA [47], the epithelial layer can be separated from the hCF, allowing for a more precise analysis of both cell groups; and (3) the lack of inclusion of any exogenous scaffold, collagen or synthetic, reduces any interference due to an added substrate and improves the physiological relevance of this system in the study of biological interactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that our corneal co-culture constructs re-capitulated epithelial-stromal interactions during wound healing with clear evidence of extracellular vesicle secretion and deposition of provisional matrix proteins between epithelial and stromal layers. Similar to our findings using endothelial-stromal co-cultures [46], diffusion and uptake of extracellular vesicles within the stroma appeared to occur, suggesting that vesicle migration is not inhibited or limited by the stromal ECM, which is composed predominately of collagen types I and V. The use of this co-culture system as a model of human wound repair has many advantages: (1) it uses human cells and can be easily manipulated to knock-in or -down genes in either the hCEC or hCF; (2) by treating the cultures with EDTA [47], the epithelial layer can be separated from the hCF, allowing for a more precise analysis of both cell groups; and (3) the lack of inclusion of any exogenous scaffold, collagen or synthetic, reduces any interference due to an added substrate and improves the physiological relevance of this system in the study of biological interactions.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, while multiple pathways are involved in corneal scarring and regeneration, targeting the myofibroblast appears to be key to this endeavor [56,57]. The appearance of extracellular vesicles during corneal wound healing [4,46] warrants further study to determine if these membrane-bound factors favor corneal regeneration by increasing matrix deposition and influence myofibroblast persistence. Our results suggest that this co-culture system may be useful in studying epithelial-stromal cell interactions during corneal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors of conjunctiva and cornea, basal cell carcinoma of the eyelid, squamous cell carcinoma, hemangioma, intraocular lymphomas, and lacrimal gland tumors are other types of eye cancers. Exosomes derived from the corneal epithelium, corneal keratinocytes, and stroma are involved in cell-cell communication, migration, cell proliferation, and wound healing [ 75 , 76 , 77 ]. Pterygium, a surface lesion from conjunctiva towards the cornea, is due to the proliferation and ECM remodeling.…”
Section: Eye Cancersmentioning
confidence: 99%
“…Cell-cell communication between the epithelial and stromal layers within the cornea directly influences corneal scar development. 16 In vivo, wounded corneal epithelium secretes extracellular vesicles (EVs) in response to epithelial debridement that is apparently restricted by the basement membrane; however, in the absence of a basement membrane (upon keratectomy), these EVs freely disperse into the corneal stroma. 17 EVs are involved in several corneal functions.…”
Section: Introductionmentioning
confidence: 99%